Polskie teatry w Moskwie (1915–1918) - Katarzyna Osińska (Pamiętnik Teatralny, 2017)
The article and the annex it is supplied with presents a little-known episode in the history of Polish theatre during the First World War. In July 1915, when the German army was drawing close to Warsaw, a part of the population was evacuated to Russia. The refugees included a number of people of the theatre, with such outstanding individuals as Stefan Jaracz, Juliusz Osterwa, Mieczysław Limanowski, Wojciech Brydziński, Wincenty Drabik, Arnold Szyfman, and others. The first Polish theatre was launched in Moscow in September 1915. The present reconstruction of this and other Polish theatre endeavours in Moscow is based on the body of known and published Polish sources as well as on previously unknown and unpublished in Poland Russian press reviews. The annex comprises reviews of Polish theatre premieres and reports about Polish-Russian cultural undertakings that appeared in the following Russian weeklies and dailies: Russkiye vedomosti, Rampa i zhizn, Teatr, Teatralnaya gazeta, and Kievskaya mysl. The last of these, a Russian-language daily published in Kiev, featured a large article about Polish drama, with a special emphasis on Stanisław Wyspiański, written by Yakov Tugenhold. All the texts have been found as a result of on-site library searches of Russian press archives; except for the article by Tugenhold, they have not been reprinted in Russia.